Chapter Un ponte tra ottomani e cristiani. Il network degli ebrei di Ragusa tra Balcani e Adriatico (1585-1635) - Ligorio, Benedetto (Atti delle «Settimane di Studi» e altri Convegni, 2019)
The research analyzes the network of the Ragusan Jews between the end of 16th and the begin of 17th century. It focalized the social and economic links of the Sephardic group as "trait d'union" of the Adriatic-Balkan trade networks. The research is focused on time frame 1585-1635 in chronological continuity to the studies of Alberto Tenenti, indeed he was the first scholar to draw the attention to the turning point of the trade structure in the Republic of Ragusa in the year 1590 because the arise of the Sephardic merchants.